Faciologia inter-recifal e geomorfologia dos recifes submersos da plataforma interna de Abrolhos, Bahia-Brasil - Leite, Marcos Daniel de Almeida (2015)
The presente study deals with geomorphic and sedimentology heterogeneity along the inner shelf of Abrolhos Shelf, Brazil. A combined analysis of side scan sonar, granulometric measurements and sub-bottom profiling characterized the facies heterogeneity of the study area. The results indicated a terrigenous to mixed supply at the Inner Arc and Abrolhos Channel. Outer Arc is represented by pure carbonate sediments. The seabed morphology were represented by different areas such as pinnacles, bank reefs, rhodoliths, pinnacles associated with rhodoliths, mesofhotic reefs and unconsolidated sediment (without reef structures). Pinnacles showed the highest heterogeneity facies in the study area, represented by all carbonate classes of sediment classification based on Larsonneur, while the Dunham classification were represented by wackstone, packstone and grainstone. Banks reefs for the most part is characterized by an muddy inter-reef facies (calcareous mud – Larsonneur/ wackstone and packstone – Dunham). Mesofhotic reefs are represented by a muddy and sandy inter-reef sedimentology while rhodoliths by gravelly deposits. The unconsolidated sediment were represented by two sedimentation patterns, muddy sediments in the Inner Arc and carbonate sandy (grainstone) at the Abrolhos Channel. Lastly, a facies distribution model is presented to the inner shelf of Abrolhos. Mixed sediments make up the Inner Arc, while Abrolhos Channel presents an extensive range of wackstones and packstones regions at the windward side of Inner Arc, those associated with reef structures (boundstone). Grainstones are near the leeward side of the Outer Arc. The Outer Arc samples are represented by a transition of boundstones (rhodoliths), grainstones (pinnacles) and wackstone/packstone (pinnacles, bank reefs and mesofotic reefs).